Mining Exploitation from the Perspective of Sharia Economic Law: An Analysis of Maslahah and Mafsadah - Nurhidayat; Kurniati; Rasdiyanah; Pikahulan, Rustam Magun; Othman, Muhammad Remy (Fawaid : Sharia Economic Law Review, 2026)
The study aims to analyze the practice of natural resource exploitation in Indonesia’s mining sector from the perspective of Sharia economic law, particularly through the concepts of maslahah (Benefit) and mafsadah (harm). The research focuses on assessing the extent to which mining activities generate not only economic benefits but also environmental, social, and distributive justice implications in natural resource governance. This study employs a qualitative design using a library research approach. Data were collected from statutory regulations, scholarly journal articles, books, official reports, and relevant Islamic legal literature. The data analyzed using a descriptive-analytical approach through content analysis in order to connect empirical findings on mining practices with the normative framework of Sharia economic law. The findings indicate that Indonesia’s mining sector makes an important contribution to economic growth, particularly in supporting industrial expansion and investment. However, these benefits do not fully reflect public maslahah, as they are accompanied by environmental degradation, deforestation, pollution, social conflict, public health risks, weak governance, and unequal distribution of benefits among communities living near mining areas. From the perspective of Sharia economic law, such conditions suggest that mining practices tend to lean more toward mafsadah when economic gains are not balanced by ecological responsibility, community protection, and distributive justice. The limitation of this study lies in its reliance on library-based research, which is not supported by direct field verification. The originality of this study lies in its effort to integrate Sharia economic law with issues of mining, environmental governance, and social justice within a more applicable framework of maqasid al-syariah. Keywords: Exploitation; Mining; Sharia Economic Law.